Carbocatalytic activation of persulfate for removal of antibiotics in water solutions - Kang, J.; Duan, X.; Zhou, L.; Sun, Hongqi; Tadé, M.; Wang, S. (2016)
Emerging pharmaceutical contaminants have raised severe challenges to remediation technologies for water treatment. In this paper, we report a facile method for preparation of nitrogen doped reduced graphene oxide (N-rGO) using urea as a nitrogen precursor. The prepared metal-free N-rGO is able to efficiently activate persulfate (PS) to produce reactive radicals for degradation of an antibiotic of sulfachloropyridazine (SCP). The effects of reaction parameters on SCP degradation were investigated. The activation processes were studied by in situ electron paramagnetic resonance (EPR), which discovered the newly observed hydroxyl radicals from PS activation. This study suggests a green remediation for removal of antibiotics in wastewater without producing any heavy metal leaching as the secondary contamination.